Pengaruh kualitas Udara ( Debu,COx, NOx, SOx) Terminal Terhadap Gangguan Fungsi Paru Pada Pedagang Tetap Terminal Bus Induk Jawa Tengah, 2002 - Soedjono, Soedjono; Setiani, Onny; Wahyuningsih, Nur Endah (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2003)
ABSTRACT Background : The high growth of motor vehicle in Central Java in 2000 reached 11,8% a year and from these number the city bus, 4,5%. This condition has seriously brought negative effect to environment. Many researchers found that the equipment of transportation and the industry are sources of air pollution, which very large and very dominant. The bus terminal is one location that is the highest air pollution than other locations because the bus terminal is a central of activities that need a transportation service. Beside that the bus terminal is a influence of sir quality dust, COx, NOx, SOx, in the bus terminal to the lung dysfunction of the permanent seller in the 15 prime bus terminals in Central Java, 2002 and to find the exposed duration, the work duration, the habit of smoking and age which can influence the lung disfunction. Method : This was an analytic research using cross sectional approach. The samples of this research were 309 respondents (total population). The concentration of dust, COx, NOx, SOx, was directly measured in the 15 prime bus terminals. The other data was measured by interviewing with the sellers in the bus terminal who had been limited their ages (40 years old to down). The logistic regression analysis was used to test the influence of dust, COx, NOx, SOx, the exposed duration, the work duration, the habit of smoking and age. Result : The result of descriptive analysis shows that all variables have influence to the instance of the lung disfunction. It can be seen from the number of percentage of respondent who experienced the lung disfunction in each variable. From analitical statistic, only the variable of anamnesis / the other diseases has influence which very significant to the instance of the lung disfunction. Other variables are risk factors to the instance of the lung disfunction. Key word : Dust, COx, NOx, SOx, concentration, interference lung – function, Seller, Bus Terminal.